(untitled) (Research, Society and Development, 2021)
Care at the end of life brings out the need to know how terminality is seen in medical training, with special attention to students’ behavoir. This gives us a better understanding of the factors associated with caring in the context of terminality. This cross-sectional study evaluated the assessment of the teaching of terminality of 347 students from the medical universities in Curitiba-PR, being composed by 72.8% of women and 43.8% of academics from the clinical period. Linear regression showed that female gender (β:-0.290; p<0.0001) and student satisfaction with their curriculum (β:-0.111; p=0.03) are the main predictors of positive attitudes towards terminality. Therefore, the role of universities in developing well-planned curricula focused on quality teaching is essential. Finally, the association with gender indicates the possibility of different models of care being present and some of them more aligned with terminality.